Development and Validation of the Empathy _x000D_ Scale in Marriage for Turkish Cultural Context - (:unkn) unknown (My University, 2021)
The study aims to develop the scale of empathy in marriage. For the validity and reliability analysis of the scale, 638 data were collected from three different sample groups. To test the construct validity of the scale, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and Criterion validity analysis were performed. Cronbach Alpha internal consistency coefficient was calculated for reliability. Result of the EFA indicated that the scale is one-dimensional and has good load values. The one-dimensional structure of the scale explains 50% of the total variance. Acceptable fit indices [χ2/df = 2.977, RMSEA= .075, SRMR= 0.05, CFI= 0.954, RFI= 0.897, IFI= 0.954] was obtained in CFA. Criterion validity analysis shows that the scale has criterion validity (r= .472; p< .001). The Cronbach Alpha internal consistency coefficient (.876) of the scale shows that the reliability of the scale is high. The results obtained from the study show that the marital empathy scale is valid and reliable.

Bu çalışmanın amacı evlilikte empati ölçeğinin geliştirilmesidir. Ölçeğin geçerlik ve _x000D_ _x000D_ güvenirlik analizleri için üç farklı örneklem grubundan toplam 638 veri toplanmıştır. _x000D_ _x000D_ Ölçeğin yapı geçerliğini test etmek için Açımlayıcı Faktör Analizi (AFA), Doğrulayıcı _x000D_ _x000D_ Faktör Analizi (CFA) ve Ölçüt geçerliği analizi yapılmıştır. Güvenirlik için Cronbach Alpha _x000D_ _x000D_ iç tutarlık katsayısı hesaplanmıştır. Açımlayıcı faktör analizi sonucunda ölçeğin tek _x000D_ _x000D_ boyutlu olduğu ve iyi yük değerlerine sahip olduğu görülmüştür. Ölçeğin tek boyutlu _x000D_ _x000D_ yapısı toplam varyansın %49,984’ünü açıklamaktadır. Doğrulayıcı faktör analizinde kabul _x000D_ _x000D_ edilebilir uyum indeksleri [χ2/sd= 2.977, RMSEA= .075, SRMR= 0.05, CFI= 0.954, RFI= _x000D_ 0.897, IFI= 0.954] elde edilmiştir. Ölçüt geçerliği analizi ölçeğin ölçüt geçerliğine sahip _x000D_ _x000D_ olduğunu göstermektedir (r=.472; p<.001). Ölçeğin Cronbach Alpha iç tutarlık katsayısı _x000D_ _x000D_ (.876) ölçeğin güvenirliğini yüksek olduğunu göstermektedir. Çalışmadan elde edilen _x000D_ _x000D_ sonuçlar evlilikte empati ölçeğinin geçerli ve güvenilir olduğunu göstermektedir.
Türkiye Kültürü Bağlamında Evlilikte Empati Ölçeğinin Geliştirilmesi ve Geçerliliği